A Revolutionary Road Map for Obesity Management and Beyond: Tirzepatide as a Dual-Acting Insulinotropic Polypeptide - Al-Ameri, Laith Thamer; Hameed, Ekhlas Khalid; Dulaimi, Ziyad; Abdalgbar, Asgad; Wahdan, May Yousif; Al Joboory, Ali; Mahmoud, Sawsan; Abdulla, Maysaa; Alshara, Luay; Al-Dulaimi, Nada Faisal (AL-Kindy College Medical Journal, 2024)
Tirzepatide is a revolutionary and promising medication with a high impact in the treatment of Obesity and T2DM with their complications. Its efficacy was proven through different trials in achieving favorable weight loss and a significant reduction in glycemic index. It also treated a large diversity of related co-morbidities, including fatty liver, cardiovascular disease, dyslipidemia, and more. Tirzepatide is well tolerated, has a good safety profile, and is highly reliable and suitable for use in a population.